Dimensions of eWOM credibility on the online purchasing activities among consumers through social media - Nor Amira Baharuddin,; Mohammad Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Word of mouth (WOM) communication has become a thoughtful information-sharing medium which can affect consumers’ buying decisions and attitudes in the direction of product categorizations and brands. Conventional word of mouth (WOM) is an outdated method for sharing thoughts and has existed as far back as individuals traded data which now evolved to the new form of word of mouth which is the electronic word of mouth (eWOM). This study attempts to analyse the dimensions of eWOM credibility on online purchasing activities among consumers through social media. This study employs a quantitative method as the paradigm of methodology in gathering the data for this research. The questionnaires were distributed to 260 respondents. The result of this study has been analysed well as aligned with the research questions as well as the research objectives. The analysis revealed that all three major dimensions which are quality, rating and recommendation consistency had significantly underpinned the eWOM credibility on the online purchasing activities among consumers through social media and a new measurement model also had been developed. The relationship between the dimensions and the differences in the dimensions between consumers of different age and gender were also being analysed in this study where each condition showed dissimilar but accurate results. All the research questions had been thoroughly answered and the research objectives of this research had achieved as well. It is hoped that this study may contribute to the related field in the future.